(untitled) (University Journal of Zoology, Rajshahi University, 2012)
A study was carried out in Faridpur, Habiganj and Barisal to identify the prevalence of diseases, morbidity and mortality of Black Bengal goats (BBGs) under semi-intensive system reared by moderate and ultra poor households in Bangladesh during the period from February 2008 to July 2009. A total of 168 female goats and 9 bucks were recorded from two types of households of which 125 goats were infected (74.70%) by a number of diseases and lead to mortality (17.26%). Survival rates and mortality percentage of kids were 80.60 and 19.40, respectively but the highest mortality was in Habiganj (21.18%). Seasons had special influences on mortality of adult goats (35.81%) and kids (64.19%) where the highest mortality rates were 22.22% and 25.93%, respectively in rainy season. PPR had the highest mortality rates (37.93% in adults and 25.00% in kids) followed by pneumonia (24.14% and 21.15%, respectively). Predator invasion was the other remarkable cause for increased kids mortality (23.08%). The study suggests that hygienic management practices, adequate supply of nutrients, and vaccination and deworming programmes in semi-intensive rearing system of BBGs at rural level will improve the survival rates of adult goats and kids. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10702 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 01-04